The relationship between social support and psychological crisis vulnerability among family impoverished undergraduates: the intermediary role of psychological resilience - Weimin Yuan; Jinhui Ning; Mengke Huo; Yiwei Feng (Frontiers in Public Health)
BackgroundFamily impoverished undergraduates are more likely to be vulnerable to psychological crises. Therefore, this study aimed to elucidate the intrinsic relationship between social support, psychological resilience, and psychological crisis vulnerability among family impoverished undergraduates and to provide valuable practical evidence and policy support for effectively improving the mental health of family impoverished undergraduates.MethodsThis study applied quantitative methods to explore the impact of social support on psychological crisis vulnerability among family impoverished undergraduates while also examining the mediating effect of psychological resilience in this process. First, we used the Psychological Crisis Vulnerability Measurement Questionnaire to assess the psychological crisis vulnerability among family impoverished undergraduates and compared it under different demographic characteristics. Second, we expanded the independent variables that affect psychological crisis vulnerability among family impoverished undergraduates and conducted multiple linear regression analyses. Finally, we employed a structural equation modeling approach to analyze the underlying mechanisms between social support and psychological crisis vulnerability and to test the conspicuousness of the mediating role of psychological resilience in the process by which social support affects psychological crisis vulnerability.ResultsAnalysis of 1,549 valid questionnaires revealed that the overall level of psychological crisis vulnerability among family impoverished undergraduates was moderate. Among the surveyed family impoverished undergraduates, 37.62% reported difficulty in maintaining psychological balance when facing crises, and 4.73% showed a very vulnerable response to crises. Factors significantly associated with the psychological crisis vulnerability of family impoverished undergraduates included being a student from a financially disadvantaged background, coming from a single-parent family, and having experienced being a left-behind child. Additionally, the participants had a social support score of 60.29 ± 11.31, indicating that individual social support was significantly correlated with family support, friend support, and support from significant others. This study confirms that social support can indirectly predict psychological crisis vulnerability of family impoverished undergraduates through psychological resilience.ConclusionFamily impoverished undergraduates are more prone to psychological crises, and effective social support can help transform them into motivational forces for their own development. This, in turn, can improve their psychological state when facing problems, and enhance their ability to solve them. Furthermore, social support influences the psychological crisis vulnerability of family impoverished undergraduates through psychological resilience. Therefore, we suggest that universities pay attention to the developmental needs of students’ subjectivity, strengthen their psychological and behavioral training, further improve psychological counseling stations, and provide group counseling to students, as appropriate. Simultaneously, attention should also be paid to students’ family issues, helping create a positive family environment for students and strengthening home-university cooperation to effectively intervene in undergraduates’ psychological crises.